Current perspectives in endoscopic vessel harvesting for coronary artery bypass grafting. (November 2011) - Kempfert, Jörg; Rastan, Ardawan; Leontyev, Sergey; Luduena, Martin; Van Linden, Arnaud; Arsalan, Mani; Blumenstein, Johannes; Holzhey, David; Lehmann, Sven; Mohr, Friedrich W; Walther, Thomas
Coronary artery bypass grafting is still the most commonly performed procedure in cardiac surgery. Minimally invasive or endoscopic vessel harvesting was developed a decade ago. It has been shown that these less traumatic techniques significantly reduce wound healing problems and improve patient satisfaction. However, there are some concerns regarding bypass patency and long-term outcomes. The aim of this article is to describe the historic development of endoscopic vessel harvesting, different harvesting techniques and to give an update of the scientific evidence and the current debate regarding outcome and safety of these minimally invasive techniques.